IDDF2019-ABS-0078 A pre-operative prognosis score for advanced hepatocellular carcinoma (hcc) patients underwent resection. (June 2019) - Xiao, Han; Wei, Mengchao; Chen, Shuling; Peng, Zhenwei; Peng, Sui; Kuang, Ming
Abstract : Background: Previous studies demonstrated a promising prognosis of advanced hepatocellular carcinoma (HCC) patients underwent surgery, yet a consensus of appropriate criteria for surgery was unreached. This study aimed at establishing a prognostic score to select candidates for surgery in advanced HCC. Methods: From May 30 th, 1995 to June 1 st, 2017, 496 advanced HCC patients who initially underwent liver resection were consecutively collected at the First Affiliated Hospital of Sun-Yat Sen University. Patients were randomly divided into the training group (n=347) and the validation group (n=149). Least absolute shrinkage and selection operator (LASSO) regression followed by a stepwise analysis were performed to select pre-operative factors to build a prognostic score for recurrence-free survival (RFS). Results: Seven factors were selected to construct the score, which were the albumin-bilirubin (ALBI) grade≥2, tumor size≥5 cm, the number of tumor-invaded liver segment≥3, hemoglobin<100g/L, gamma-glutamyl transpeptidase≥50U/L, alpha fetoprotein≥200 mg/L and portal vein tumor thrombus stage≥3. The training group was separated into the low-risk (score<14, n=148) and high-risk groups (score≥14, n=199). The median RFS of the low-risk group was significantly longer than that of the high-risk group (10.1 vs 2.9 months, P<0.001). In the validation group, median RFS of the low-risk group was 13.7 months, significantly longer than the high-risk group (4.6 months, P=0.002). The C-index of this score was 0.726. Conclusions: Surgery could provide promising survival for selective HCC patients in the advanced stage. We constructed a well-validated score to identify appropriate candidates for surgery in the advanced HCC patients. Surgery for patients in the low-risk group is recommended according to our results.